Post-infectious IBS: Defining its clinical features and prognosis using an internet-based survey. Issue 8 (October 2018) - Card, Tim; Enck, Paul; Barbara, Giovanni; Boeckxstaens, Guy EE; Santos, Javier; Azpiroz, Fernando; Mearin, Fermin; Aziz, Qasim; Marshall, John; Spiller, Robin
Background: Gastrointestinal infection is an important risk factor for developing irritable bowel syndrome (IBS). Our aim was to characterise post-infectious IBS (PI-IBS) compared to other IBS patients. Methods: An internet survey of IBS patients using Rome III diagnostic questionnaire, Hospital Anxiety and Depression Scale (HADS) and Patient Health Questionnaire-12 Somatic Symptom (PHQ12-SS) scale score documenting the mode of onset was conducted. Results: A total of 7811 participants (63.2% female), of whom 1004 (13.3%) met criteria for PI-IBS, were studied. Seventy per cent of PI-IBS patients described sudden onset, 35% onset while travelling, 49.6% vomiting, 49.9% fever and 20.3% bloody diarrhoea. Compared to other IBS individuals, PI-IBS was significantly associated with living in Northern Europe and North America, having a hysterectomy, not having an appendicectomy, higher PHQ12-SS score and having more than one toilet in the family home. PI-IBS patients had more frequent stools. At one year recovery rate in the PI-IBS and non-PI-IBS group was 19.7% and 22.2%, p = 0.15. Recovery rates were lower for females (20.7%) vs males (38.8%), those with somatisation (23.0%) vs those without (33.2%) and those living in North America or Northern Europe (21.1%) vs living elsewhere (33.9%) p ≤ 0.001. Conclusion: PI-IBS accounts for around 13% of all IBS in this internet sample, with some distinctive features but a similar prognosis to the remainder.